IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA ARAB DI PERGURUAN TINGGI KEAGAMAAN ISLAM: STUDI KASUS DI UIN AR-RANIRY BANDA ACEH - Siti Rahmah (lembaga Sepercenter, 2026)
The Merdeka Curriculum is a strategic educational policy in Indonesia designed to improve learning quality through a flexible, student-centered, and competency-based approach. In Islamic higher education, its implementation in Arabic language learning presents both opportunities and challenges in developing students' communicative competence, collaboration, and adaptability to technological advancement. This study aims to analyze the implementation of the Merdeka Curriculum in Arabic language learning at Universitas Islam Negeri Ar-Raniry Banda Aceh, focusing on instructional planning, implementation, assessment, supporting factors, and implementation challenges. This study employed a qualitative case study approach. Data were collected through classroom observations, in-depth interviews with lecturers and students, and documentation analysis of Semester Learning Plans (RPS), teaching modules, and learning documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the Merdeka Curriculum has promoted more active learning through Project-Based Learning, Case-Based Learning, collaborative discussions, and digital learning media. Learning planning has integrated Graduate Learning Outcomes and Outcome-Based Education principles. However, several challenges remain, including limited digital learning facilities, diverse student competencies, and varying levels of lecturers' readiness to implement project-based learning effectively. The study recommends strengthening lecturers' professional competence, developing digital Arabic learning resources, and enhancing institutional support to ensure sustainable implementation of the Merdeka Curriculum.